Reflections on the ethics of social experimentation - Macartan Humphreys (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Social scientists are increasingly engaging in experimental research projects of importance for public policy in developing areas. While this research holds the possibility of producing major social benefits, it may also involve manipulating populations, often without consent, sometimes with potentially adverse effects, and often in settings with obvious power differentials between researcher and subject. Such research is currently conducted with few clear ethical guidelines. In this paper I discuss research ethics as currently understood in this field, highlighting the limitations of current approaches and the need for the construction of appropriate ethics, focusing on the problems of determining responsibility for interventions and assessing appropriate forms of consent.
Keywords: C90; C93; 330; field experiments; ethics; human subjects; consent